ODGJ KARENA NARKOBA - Ika Apriani Fadilah; Yahdinil Firda Nadhirah (STKIP Subang, 2024)
The Dira Sumantri Toha Foundation is a rehabilitation institution that focuses on treating people with mental disorders (ODGJ) who are also addicted to drugs. The Dira Sumantri Toha Foundation has been operating for more than a decade and has treated hundreds of patients with various mental disorders and drug addiction. This foundation provides various services, including psychological therapy, counseling, and structured rehabilitation activities. This research aims to understand more deeply the treatment methods applied by the foundation and the challenges faced in treating ODGJ who are related to drugs. This research uses a case study design with a qualitative approach. A qualitative approach was used to explore more in-depth and detailed information regarding patient experiences and treatment methods applied at the Dira Sumantri Toha Foundation. The treatment methods applied by the foundation show positive results in reducing symptoms of mental disorders and improving the patient's quality of life. The case study of Patient A shows that the integration of multiple therapeutic approaches can provide significant results in the recovery process.